The future of copyright in the age of artificial intelligence - Gaon, Aviv H. (Elgar law, technology and society, 2021)
"The Future of Copyright in the Age of Artificial Intelligence offers an extensive analysis of intellectual property and authorship theories and explores the possible impact artificial intelligence (AI) might have on those theories. The author makes compelling arguments via the exploration of authorship, ownership and artificial intelligence. First, the book advocates for a more holistic approach to authorship, arguing that there is no good reason to exclude computer-generated and AI creations from copyright. Second, it conducts an open search for the right 'candidate' for ownership. In doing so, the book explores several possible legal frameworks, including assigning ownership to the programmer, the user, the AI itself and other alternatives such as the public domain or author-in-law approaches. Third, the book explores the concept of AI as it has developed through the years in various fields, seeking to reframe the AI legal concept. For academic scholars and law students these pages frame the theoretical debate about AI creations and provide in depth discussion about AI legal challenges"--